The Use of Acoustic Vectors Decomposition of Sound Fields to Vibroacoustic Protection on Ships - WEYNA, Stefan (Archives of Acoustics, 2017)
In this paper, numerous examples will be illustrated as principles of applying the sound intensity measurements to practical problems at the noise abatement on ships and offshore constructions. The paper presents the results of transmission loss measurements together with flanking transmission for ship bulkheads and partitions with doors and windows. Investigations carried out with sound intensity measurement techniques will be compared against those made by classical methods. Finally for a few examples, the graphic presentation of spatial distribution of sound intensity vectors risen close to vibrating ship cabin partitions and inside the cabin will be shown in 2D and 3D graphical form. As a result, a two-dimensional acoustic wave flow map of time-averaged active intensity vectors propagated along curved streamlines and a vector perpendicular to measured plane are graphically illustrated. The technique of acoustic vectors decomposition of sound fields described, can enrich the knowledge of the mechanism of acoustic energy flux through ship partitions.